BNI Marketing Strategy for Credit Cards in Dealing Global Competition in State Bank Indonesia (Persero) Tbk Banda Aceh Branch Office - Erry Dianto; Saibul Anwar; Husnawati Husnawati; Zurnalis Zurnalis (Budapest International Research and Critics University, 2020)
This study aims to analyze the marketing strategy of BNI Credit Cards in the face of global competition at PT. Bank Negara Indonesia (Persero) Tbk Banda Aceh Branch Office. This study uses a qualitative approach with a descriptive type where the type of data used is secondary data sourced from various reports and documentation from PT. Bank Negara Indonesia (Persero) Tbk Banda Aceh Branch Office. The results of this study indicate that in marketing BNI Banda Aceh Branch credit cards a strategy that can be used is a marketing strategy that differentiates the market (Differentiated marketing), which is to determine the target market segmentation in accordance with the target types of credit card products that are in accordance with the segmentation. The Banda Aceh BNI branch also uses a concentrated marketing strategy such as the marketing of BNI-Unsyiah affinity Credit Cards which is focused on alumni of Syiah Kuala University throughout Indonesia. Besides that, another strategy used by the Banda Aceh BNI branch in marketing BNI Credit Cards is by issuing pre aproval credit cards, where certain customers in accordance with applicable regulations are directly proposed to issue credit cards on behalf of these customers, if the customer agrees for card issuance, the card can be activated immediately. Furthermore, BNI provides the convenience of non-cash transactions through the YAP (Your All Payment) application as a payment tool for (cashless) and without showing the debit card or credit card (Cardless) through a smartphone. This YAP application is an advantage owned by BNI and the first in Indonesia.